2018
DOI: 10.1097/mph.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

Is MPV a Predictive Marker for Neonatal Sepsis? A Pilot Study

Abstract: Neonatal sepsis (NS) continues to be a diagnostic challenge and a prime cause of mortality. Forage for a lucid, cost-effective yet highly sensitive and specific marker in diagnosing this entity is an incessant task. This study aimed to evaluate the predictive value of mean platelet volume (MPV) in diagnosing NS. Neonates diagnosed with sepsis from January 2016 to March 2016 were included in the study. The subjects were stratified into the following: (i) culture-proven sepsis (group I); (ii) culture-negative cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
5
18
1
3
Order By: Relevance
“…Second, we could not investigate the relationship between platelet parameters and sepsis because few of our preterm infants had sepsis at birth and we did not investigate changes of platelet parameters during the postnatal period. Some studies associated sepsis with elevated MPV in neonates during the postnatal period [32,34]. Third, Apgar score was not associated with lower PLT in late preterm and term neonates in this study.…”
Section: Plos Onecontrasting
confidence: 51%
“…Second, we could not investigate the relationship between platelet parameters and sepsis because few of our preterm infants had sepsis at birth and we did not investigate changes of platelet parameters during the postnatal period. Some studies associated sepsis with elevated MPV in neonates during the postnatal period [32,34]. Third, Apgar score was not associated with lower PLT in late preterm and term neonates in this study.…”
Section: Plos Onecontrasting
confidence: 51%
“…In this study, PCT is an independent risk factor for IVH. To date, previous research suggested that PCT had a predictive value for RDS in preterm newborns (27). However, few studies investigated the relationship between PCT and IVH.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, it has been demonstrated that platelets with higher MPV values have a larger surface area and more granules, which is associated with their activation [32]. Furthermore, MPV, MPV/PLT, and PLR were considered as diagnostic adjunct tests for BSI [33][34][35][36]. Nevertheless, Johansson et al have reported that there was no association between bacterial species and the occurrence of thrombocytopenia [37].…”
Section: Discussionmentioning
confidence: 99%